2020
DOI: 10.1093/biolinnean/blaa159
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic alkaloid in pollen and nectar excludes generalist bees from foraging at death-camas,Toxicoscordion paniculatum(Melanthiaceae)

Abstract: Many plants produce broadly active toxins to which specialist herbivores—typically insects—have evolved counter-adaptations, sometimes spawning co-evolutionary arms races. Many non-social bee species are likewise taxonomic host specialists, but the specialists’ pollen hosts frequently attract diverse floral generalists as well, even to flowers of plants that are otherwise chemically defended. In this study of foothills death-camas, Toxicoscordion paniculatum (Nutt.) Rydberg (formerly Zigadenus), we show that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…Thus, the pollen used by specialists is not avoided by generalists. Our results contrast with previous studies that focused on single genera or families of specialist host plants and found that generalist bees did not collect pollen from these plants (specifically, plants in the genera Cucurbita [Brochu et al, 2020] and Toxicoscordion [Cane et al, 2020], and in the family Asteraceae [Müller & Kuhlmann, 2008; Praz et al, 2008]). By sampling a wider range of host plant taxa, our study provides a broader test of the pollen quality hypothesis, and our results are consistent with those of another study that sampled a range of host plant taxa used by bees in the genus Andrena (Wood & Roberts, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the pollen used by specialists is not avoided by generalists. Our results contrast with previous studies that focused on single genera or families of specialist host plants and found that generalist bees did not collect pollen from these plants (specifically, plants in the genera Cucurbita [Brochu et al, 2020] and Toxicoscordion [Cane et al, 2020], and in the family Asteraceae [Müller & Kuhlmann, 2008; Praz et al, 2008]). By sampling a wider range of host plant taxa, our study provides a broader test of the pollen quality hypothesis, and our results are consistent with those of another study that sampled a range of host plant taxa used by bees in the genus Andrena (Wood & Roberts, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…The first hypothesis proposes that bees specialize on plants whose pollen is avoided by other bees. According to what we will call the "pollen quality hypothesis," pollen-specialist bees developed adaptations to feed on plants with low-quality pollen-pollen that possesses secondary compounds or other deterrents (Irwin et al, 2014;Rivest & Forrest, 2020;Stevenson, 2020) or that is low in protein content-and is thus avoided by other bee species (Brochu et al, 2020;Cane et al, 2020;McAulay et al, 2020;Müller & Kuhlmann, 2008;Praz et al, 2008;Trunz et al, 2020;Vanderplanck et al, 2020). This strategy could evolve to allow the bee to use an unexploited resource (Danforth et al, 2019), because low-quality and/ or defended pollen protects the bee and its offspring from brood parasites or fungal pathogens (Bernays & Graham, 1988;Giacomini et al, 2018;LoCascio et al, 2019;Spear et al, 2016;Wynns, 2012) or because a coevolutionary arms race occurred between the bee and its host plant during their evolutionary history (Danforth et al, 2019;Wcislo & Cane, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also contain various plant metabolites, including alkaloids, that may act as repellents for herbivores and exhibit bactericidal and fungicidal properties. [58][59][60] In particular, Ha, Hol, and Hlol have been reported to have anti-herbivory properties against lepidopteran larvae, 61-64 as well as a significant antimicrobial activity. 25,34,[39][40][41] Therefore, their presence in the anthers could be related to their potential role either as repellent and/or antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Anthers are reproductive structures in plants that contain pollen, which is essential for plant reproduction. They also contain various plant metabolites, including alkaloids, that may act as repellents for herbivores and exhibit bactericidal and fungicidal properties 58–60 . In particular, Ha, Hol, and Hlol have been reported to have anti‐herbivory properties against lepidopteran larvae, 61–64 as well as a significant antimicrobial activity 25,34,39–41 .…”
Section: Discussionmentioning
confidence: 99%